From red scare to yellow peril - Svetličič, Marjan (Teorija in praksa, 2020)
China is the greatest challenge facing the world today. Yet fears of the yellow peril are not new. They started with fear of the rise of Bolshevism and later the Soviet Union after World War II (the red scare) and European fears of the USA becoming dominant following WW2 and the subsequent fear of the spectacular technological rise of Japan. The article shows that considerable differences exist among such challengers in their size, political system, ideological basis, military strength, geopolitical ambitions and, finally, cultural differences. These fears have proven to be overblown. Still, they play a positive role as a wakeup call to draw attention to the need to adapt to the tectonic changes occurring in the entire world system and the strategies/policies of certain individual actors. The explanatory power of different theories with respect to certain cases is considered. Somewhere along the line, the greatest weight has been attributed to economic/quantitative factors (Japan, USA, China), ideological/military ones with respect to the Soviet Union/ Russia, while elsewhere more ethnocentric factors are stressed (Japan, China). A multidisciplinary approach is called for because a single discipline is unable to explain such tectonic changes and the ensuing reactions.
Keywords: Ethnocentrism; Etnocentrizem; Evropa; Geopolitical changes; Geopolitične spremembe; Japonska; Kitajska; prenos moči; rdeča nevarnost; rumena nevarnost; Rusija; tektonske spremembe; ZDA